A voice-activated integrated development environment for manually disabled programmers. - Langan DD; Hain TF; Hubbell TJ; Frøseth J (Disability & Rehabilitation: Assistive Technology)
Purpose. The paper presents the design and implementation of voice-based interface to support two types of application development activities (coding, and visual GUI design) by manually disabled programmers. Method. Prototype programs were implemented, and tests were performed for both proposed voice-based interface models. Results. The interface design concepts, and the results and lessons learned of the usability studies are discussed. Conclusions. The usability studies indicated that the interface models were sound, although the voice recognition aspects left something to be desired.